2010
DOI: 10.1002/hbm.21132
|View full text |Cite|
|
Sign up to set email alerts
|

Discovering the somatotopic organization of the motor areas of the medial wall using low‐frequency bold fluctuations

Abstract: bstract: This study explored the somatotopy of the motor areas of the medial wall of the cerebral hemisphere, in the human brain. In a sample of 16 healthy participants, we drew 9 regions of interest (ROI) over the primary motor area (M l), each corresponding to a well-known somatic representation. Using functional magnetic resonance imaging, we investigated the resting state functional connectivity between each selected ROI and the motor areas of the medial wall. The main finding was the identifi cation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 68 publications
(25 reference statements)
3
32
0
Order By: Relevance
“…Importantly and well in line with the current results, task-dependent functional connectivity of this region with the amygdalae and the OFC have already been shown in a previous MACM investigation (Cauda et al, 2011b). Finally, tracer studies in nonhuman primates have repeatedly demonstrated connections between amygdala and SGC (Freedman et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly and well in line with the current results, task-dependent functional connectivity of this region with the amygdalae and the OFC have already been shown in a previous MACM investigation (Cauda et al, 2011b). Finally, tracer studies in nonhuman primates have repeatedly demonstrated connections between amygdala and SGC (Freedman et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…It should be noted that MACM as a data-driven approach characterizes the co-activations of a given region of interest – independent of how this seed has been defined. That is, while MACM has most commonly been used to investigate the functional connectivity of anatomically defined seed regions (Cauda et al, 2011b; Eickhoff et al, 2010; Robinson et al, 2010), brain regions defined by functional properties as in the current study, may likewise be assessed (e.g. Jakobs et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, both sets of data show that the medial centroparietal area reacted during active control, confirming previous anatomical studies [10]. EEG spectra for this condition display most power decrease in the band.…”
Section: Discussionsupporting
confidence: 86%
“…Intrinsic functional brain connectivity, as revealed by low-frequency spontaneous fluctuations in the time courses of fMRI signals, has recently drawn much interest. Domains of correlated activity, often referred as resting state networks (RSNs), identified within the cerebral cortex, are related to specific types of sensory, motor and cognitive functions (Beckmann et al, 2005;Cauda et al, 2010b;Damoiseaux et al, 2006; see Fox and Raichle, 2007 for a review). Recently, this technique was further validated by showing very unlikely that RSNs are produced artifactually, by aliasing of cardiac and respiratory cycles; in fact, RSNs are localized in the gray matter and are likely related to ongoing neuronal activity (De Luca et al, 2006).…”
Section: Introductionmentioning
confidence: 99%